1996
DOI: 10.1038/383279a0
|View full text |Cite|
|
Sign up to set email alerts
|

Three-dimensional structure of human cytomegalovirus protease

Abstract: Herpesviruses encode a serine protease that specifically cleaves assembly protein. This protease is critical for replication, and represents a new target for antiviral drug design. Here we report the three-dimensional structure of the protease from human cytomegalovirus (hCMV) at 2.27 angstroms resolution. The structure reveals a unique fold and new catalytic strategy for cleavage. The monomer fold of the enzyme, a seven-stranded beta-barrel encircled by a chain of helices that form the carboxy terminus of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(102 citation statements)
references
References 28 publications
2
100
0
Order By: Relevance
“…2) [58,59]. The stabilization of the oxyanion hole is realized in a similar manner in all serine proteases as well.…”
Section: Assemblinsmentioning
confidence: 70%
See 1 more Smart Citation
“…2) [58,59]. The stabilization of the oxyanion hole is realized in a similar manner in all serine proteases as well.…”
Section: Assemblinsmentioning
confidence: 70%
“…The first crystal structures of an assemblin were published by three groups in 1996 [58,59,83]. All three structures are of dimeric HCMV-assemblin.…”
Section: Structurementioning
confidence: 99%
“…The amino-acid sequences of herpesvirus proteases have no detectable homology to other serine proteases or hydrolases. The crystal structure of HCMV protease has recently been determined in our laboratory by the seleno-methionyl multiple-wavelength anomalous diffraction (MAD) technique (Tong et al, 1996), and in other laboratories by the heavy-atom isomorphous replacement technique (Qiu et al, 1996;Shieh et al, 1996;Chen et al, 1996). It showed that HCMV protease possesses a new polypeptide backbone fold; confirmed that Ser132 and His63 are in close proximity in space; and identified His157 as the possible third member of the catalytic triad.…”
Section: Introductionmentioning
confidence: 95%
“…They exist in a monomer-dimer equilibrium in vitro where only the dimer is active [5][6][7]. Xray crystallographic studies on the protease from CMV, HSV1, HSV2, VZV, KSHV and EBV have shown the presence of a conserved dimer structure [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%